The role of ferroptosis in virus infections - Wang, Jing; Zhu, Junda; Ren, Shuning; Zhang, Zihui; Niu, Kang; Li, Hua; Wu, Wenxue; Peng, Chen (Frontiers in Microbiology, 2023)
Regulated cell death (RCD) is a strategy employed by host cells to defend invasions of pathogens, such as viruses and bacteria. Ferroptosis is a type of RCD characterized by excessive accumulation of iron and lipid peroxidation. While ferroptosis is primarily considered as a mechanism associated with tumorigenesis, emerging evidence begin to suggest that it may play essential role during virus infections. Recent studies illustrated that activation of ferroptosis could either induce or prohibit various types of RCDs to facilitate virus replication or evade host surveillance. More experimental evidence has demonstrated how viruses regulate ferroptosis to influence replication, transmission, and pathogenesis. This review summarizes ferroptosis-related metabolism, including iron metabolism, lipid peroxidation, and antioxidant metabolism. Furthermore, we discuss the interplay between viral infections and host ferroptosis process, with a focus on the mechanism of how viruses exploit ferroptosis for its own replication. Understanding how ferroptosis impacts virus infection can offer valuable insights into the development of effective therapeutic strategies to combat virus infections.